Interference competition pressure predicts the number of avian predators that shifted their timing of activity. Issue 1880 (6th June 2018) - Pei, Yifan; Valcu, Mihai; Kempenaers, Bart
Abstract : Being active at different times facilitates the coexistence of functionally similar species. Hence, time partitioning might be induced by competition. However, the relative importance of direct interference and indirect exploitation competition on time partitioning remains unclear. The aim of this study was to investigate the relative importance of these two forms of competition on the occurrence of time-shifting among avian predator species. As a measure of interference competition pressure, we used the species richness of day-active avian predator species or of night-active avian predator species (i.e. species of Accipitriformes, Falconiformes and Strigiformes) in a particular geographical area (assemblage). As an estimate of exploitation competition pressure, we used the total species richness of avian predators in each assemblage. Estimates of the intensity of interference competition robustly predicted the number of Accipitriformes species that became crepuscular and the number of Strigiformes species that became day-active or strictly crepuscular. Interference competition pressure may depend on body size and on the total duration of the typical active period (day or night length). Our results support—to some extent—that smaller species are more likely to become time-shifters. Day length did not have an effect on the number of time-shifter species in the Accipitriformes. Among the large Strigiformes, more time-shifter species occur in areas where nights are shorter (i.e. where less of the typical time resource is available). However, in the small Strigiformes, we found the opposite, counterintuitive effect: more time-shifters where nights are longer. Exploitation competition may have had an additional positive effect on the number of time-shifters, but only in Accipitriformes, and the effect was not as robust. Our results thus support the interference competition hypothesis, suggesting that animals may have shifted their time of activity, despite phylogenetic constraints on the ability to do so, to reduce the costs of direct interactions. Our findings also highlight the influence of body size as a surrogate of competitive ability during encounters on time partitioning, at least among avian predators.